Pediatric diaphragmatic pacing - Tarek R. Hazwani; Bedoor Alotaibi; Wadha Alqahtani; Asma Awadalla; Ali Al Shehri (MDPI AG, 2019)
Diaphragmatic pacing has been shown to play a significant role in adult patients with diaphragmatic paralysis and facilitates mechanical ventilation weaning. However, reports on its use in paediatric patients are scarce. This report is about a 4-year-old child with a spinal cord injury secondary to a motor vehicle accident that led to quadriplegia and diaphragm paralysis. The patient underwent a diaphragmatic pacing procedure, which helped start gradual weaning from mechanical ventilation. We reviewed the concept of the diaphragmatic pacer and its types depending on the site of the implantation. In addition, we reviewed who can benefit from using a diaphragmatic pacer and compared its use in adults versus paediatric patients. Our case showed that diaphragmatic pacing appears to be effective, as it facilitates mechanical ventilation weaning and improves the quality of life outcome in paediatric patients with diaphragmatic paralysis.